Analisis Manajemen Risiko Operasional pada UMKM Kebab Capadocia di Kabupaten Boyolali - Aidha Melany; Novi Lestari; Vinata Utari (Jurnal Riset dan Inovasi Manajemen, 2026)
Operational risk management is an essential aspect in maintaining the stability and sustainability of micro-enterprises operating in the culinary sector, particularly in the fast food industry, which relies heavily on production processes, raw material quality, and human resource skills. This study aims to analyze the types of operational risks that arise in the daily operations of the Kebab Capadocia MSME in Boyolali Regency using a qualitative approach through in-depth interviews and field observations. The COSO Enterprise Risk Management (ERM) Framework was used as the primary theoretical foundation to map risks based on five components: risk identification, risk assessment, control activities, information and communication, and monitoring. The results indicate that the business faces four main risk categories: production process risks, human resource risks, food hygiene and safety risks, and raw material distribution risks. Implemented controls are still informal and not supported by standard operating procedures (SOPs), resulting in recurring risks that impact product quality. These findings contribute to the MSME risk management literature and offer practical recommendations for strengthening operational structures based on systematic risk management.